A study of novel optical solutions of the space-time fractional cubic nonlinear Schrodinger equation - Ozkan, Ayten; Ozkan, Erdogan Mehmet (SPRINGER, 2024)
In this study, the space-time fractional cubic nonlinear Schrodinger equation with beta-derivative is examined using the modified (G '/G2) method, and exact optical solutions are achieved. Using this technique, many traveling wave solutions for the aforementioned equation are constructed, including hyperbolic, trigonometric, and real solutions. Thanks to this method, the solutions of the mentioned equation are found clearly and the physical behavior of these solutions is shown graphically. These dynamical models' complex physical events are helped by the method. The solutions' novel physical surface structures are offered with a variety of suitable assigned values. Graphical representations and numerical implementations are utilized to support the theoretical findings. In this way, it has been shown that the consistency of the method provides a new perspective on the mentioned equation.
Keywords: Fractional cubic nonlinear Schrodinger equation; beta-Derivative; Modified (G '/G(2))-expansion method; DIFFUSION; MODEL; Engineering; Physics; Optics